1991
DOI: 10.1007/bf00260793
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of intestinal hydrolases to starvation in rats: effect of thyroid function

Abstract: The effects of long-term starvation on the activities of sucrase, lactase, and aminopeptidase, and on their respective mRNA were determined in the small intestine of thyroidectomized and sham-operated adult rats. Thyroidectomy reduced the protein loss at the level of the intestinal brush border membranes during starvation. Prolonged fasting caused a significant decrease in sucrase activity, but thyroidectomy partly prevented this effect. However, the amount of the corresponding mRNA dropped during long term st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Profound changes occur in the gut mucosa during ileus, fasting, and starvation (Brown et al, 1960;Eastwood, 1977;Galluser et al, 1991;Goodlad et al, 1988;Gorostiza et al, Steiner et al, 1968) in parallel with complex alterations in gut motility (Telford et al, 1993). Animal and clinical studies have demonstrated that such changes are only partially reversed by parenteral nutrition (Inoue et al, 19931, while one investigator has reported the reversal of atrophic changes in defunctionalized small intestinal loops after luminal perfusion with water (Clarke, 1976).…”
Section: Discussionmentioning
confidence: 97%
“…Profound changes occur in the gut mucosa during ileus, fasting, and starvation (Brown et al, 1960;Eastwood, 1977;Galluser et al, 1991;Goodlad et al, 1988;Gorostiza et al, Steiner et al, 1968) in parallel with complex alterations in gut motility (Telford et al, 1993). Animal and clinical studies have demonstrated that such changes are only partially reversed by parenteral nutrition (Inoue et al, 19931, while one investigator has reported the reversal of atrophic changes in defunctionalized small intestinal loops after luminal perfusion with water (Clarke, 1976).…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggest that common systemic factors might be involved in regulating the expression of these enzymes. Although little is known about the factors regulating the activity of these peptidases, the role of hormonal factors has been well documented, especially in the ontogenetic maturation of the small intestine [9,10,16,24]. It seems worth speculating about the potential role of hormones as systemic regulatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…From the results of that study, we considered that the absorption of dietary protein might be preserved under conditions of malnourishment. However, studies of the adaptation of intestinal peptidases to starvation have yielded conflicting results [5,10,14,21].…”
Section: Introductionmentioning
confidence: 98%
“…The reasons for these discrepancies are not clear. In small animal studies, thyroxine increased intestinal lactase in embryogenesis [ 36 ] but later it inhibited intestinal lactase [ 37 ]. The above clinical observations could be explained by inhibition of human intestinal lactase but human studies are scarce [ 36 ].…”
Section: Symptomatic Improvement With Regular Lactose Consumption mentioning
confidence: 99%